Implementasi Media Pohon Angka Berbasis Ramah Anak untuk Meningkatkan Keaktifan Pembelajaran Anak Usia 4-5 Tahun di TKK Satu Atap Lebijaga - Nofrianus Talu Popo; Marsianus Meka; Efrida Ita; Elisabeth Tantiana Ngura (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to increase the learning activeness of children aged 4–5 years at TKK Satu Atap Lebijaga through a child-friendly number tree media. This study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model with the following steps: 1) planning, 2) implementation of the action, 3) observation, and 4) reflection. The child-friendly number tree media was implemented in the learning process, and the results were evaluated in each cycle to determine success and provide improvements for the subsequent actions. Data collection techniques included observation, assessment, and documentation. The instruments used in this study were a research instrument grid and a rubric for improving learning activeness. Data analysis techniques were conducted using descriptive qualitative and quantitative methods. The indicator of success in this study was an increase in the percentage compared to the previous action. The research results show that the implementation of child-friendly number tree media was able to significantly improve children’s learning activeness. In the pre-cycle stage, the average level of children’s activeness reached 45%, which was categorized as less active. After the intervention was carried out in Cycle I, the percentage of activeness increased to 68%, categorized as fairly active. Furthermore, in Cycle II it increased to 90%, categorized as very active. Improvements occurred across all indicators of activeness, including the courage to answer questions, active participation in learning activities, ability to use the media, enthusiasm for learning, and interaction with teachers and peers. Based on these research findings, keaktifan meningkat menjadi 68% dengan kategori cukup aktif. Selanjutnya pada siklus II meningkat menjadi 90% dengan kategori it can be concluded that child-friendly number tree media is effective in increasing the learning activeness of children aged 4–5 years at TKK Satu Atap Lebijaga.